PERSEPSI DAN MOTIVASI PENGUNJUNG NUSANTARA TAMAN NASIONAL BUNAKEN - Handoyo, Eko Wahyu; Walangitan, Hengki Djemie; Pangemanan, Paulus Adrian (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine perceptions and motivations of domestic visitors to Bunaken National Park. Data collection was carried out during September to November 2021. The research method used was a survey method with a sample of respondents taken randomly, using a purposive sampling of 150 people. The results showed that the characteristics of visitors were evenly distributed in all ages in the age range of 21-25 years, dominated by Bachelor and Senior High School, professions of private employees, entrepreneurs and civil servants, income between Rp 1.000.000,- – Rp 2.000.000 to more than Rp 5.000.000 and the number of family members between 3 - 5 people. The perception of visitors is attractive as much as 44.7% and very attractive 37.3%, the value being very important is 62.7% and important is 27.3%, visitor satisfaction convey 41.3% satisfied and 40.7% very satisfied. The motivation of visitors because of the advantages Bunaken National Park 35% a good natural tourist destination, 21% near to Manado City and 17% cheap and easy accessibility, as a reference source of visiting information 38% comes from stories of friends, 24% social media facebook, 15.3% social media instagram and 12.7% websites.